Cultural Remittances and Modern Fertility - Mickael Melki; Hillel Rapoport; Enrico Spolaore; Romain Wacziarg (CESifo GmbH, 2024)
We argue that migrants played a significant role in the diffusion of the demographic transition from France to the rest of Europe in the late 19th century. Employing novel data on French immigration from other European regions from 1850 to 1930, we find that higher immigration to France translated into lower fertility in the region of origin after a few decades - both in cross-region regressions for various periods, and in a panel setting with region fixed effects. These results are robust to the inclusion of a variety of controls, and across multiple specifications. We also find that immigrants who themselves became French citizens achieved lower fertility, particularly those who moved to French regions with the lowest fertility levels. We interpret these findings in terms of cultural remittances, consistently with insights from a theoretical framework where migrants act as vectors of cultural diffusion, spreading new information, social norms and preferences pertaining to modern fertility to their regions of origin.
Keywords: J13; F22; N13; O40; 330; migration; fertility control; social influence; cultural change; diffusion